A wearable lightweight exoskeleton with full degrees of freedom for upper-limb power assistance. (3rd April 2021) - Liu, Chang; Liang, Hongbo; Murata, Yoshitaka; Li, Peirang; Ueda, Naoya; Matsuzawa, Ryuichi; Zhu, Chi
ABSTRACT: In this paper, a novel wearable lightweight exoskeleton with full degrees of freedom for upper-limb power assistance is developed. It is controlled by surface electromyography(sEMG) signals of the agonist muscle alone and aims to provide 30% power assistance to the elbow and shoulder joints for the flexion/extension movement. In the exoskeleton, there are two wearable identical arms and a back support pack. Each arm consists of two active joints and four passive joints, in which the active joints implement the power assistance for flexion/extension movement of the elbow and shoulder joints, whereas the passive joints fully follow the wearer's other motions. Moreover, with a rotatable and telescopic mechanism, the joint axis of the elbow joint of the exoskeleton can be adjusted to coincide with the elbow joint for different wearers, and meanwhile the passive joints of the shoulder complex of the exoskeleton can guarantee its instantaneous center of rotation to coincide with that of the wearer. As a result, the developed exoskeleton eliminates the restriction of motion and then the discomfort of the wearer. In addition, an extended admittance control is introduced and the effectiveness of the power assistance is verified. GRAPHICAL ABSTRACT: